ANALISIS PENGALOKASIAN DANA DESA UNTUK MENINGKATKAN PEMBANGUNAN DESA HILIONAHA KECAMATAN ONOLALU KABUPATEN NIAS SELATAN - Fau, Samanoi Halowo (LPPM Universitas Nias Raya, 2022)
The scope of this research aims to find out and analyze whether the allocation of Village Funds to improve the Development of Hilionaha Village, Onolalu District, South Nias Regency, has been effective. This type of research is qualitative research that is descriptive. The location studied is in Hilionaha Village, Onolalu District, South Nias Regency. The data collection procedures carried out in this study are observation, interviews, and documentation. Data analysis uses analysis according to Miles and Huberman, namely data reduction, presentation, and verification. The results of this study show that the Allocation of Hilionaha Village Funds in Onolalu District of South Nias Regency for village development has been effective and in accordance with the laws and regulations. Village Funds are very useful for increasing development in Hilionaha Onolalu District, South Nias Regency. Village Funds are able to encourage progress in various aspects both in the field of economy and health. So that it can be concluded that the use of village funds 2015-2019 in Hilionaha village increases village development. The proposed suggestion is that the village head and the community are expected to support each other's village development program in accordance with existing procedures to make Hilionaha village into a village that has competitiveness to catch up with other villages that have been developed.